Intrinsically disordered regions are abundant in simplexvirus proteomes and display signatures of positive selection. Issue 1 (10th May 2020) - Mozzi, Alessandra; Forni, Diego; Cagliani, Rachele; Clerici, Mario; Pozzoli, Uberto; Sironi, Manuela
Abstract: Whereas the majority of herpesviruses co-speciated with their mammalian hosts, human herpes simplex virus 2 (HSV-2, genus Simplexvirus ) most likely originated from the cross-species transmission of chimpanzee herpesvirus 1 to an ancestor of modern humans . We exploited the peculiar evolutionary history of HSV-2 to investigate the selective events that drove herpesvirus adaptation to a new host. We show that HSV-2 intrinsically disordered regions (IDRs)—that is, protein domains that do not adopt compact three-dimensional structures—are strongly enriched in positive selection signals. Analysis of viral proteomes indicated that a significantly higher portion of simplexvirus proteins is disordered compared with the proteins of other human herpesviruses. IDR abundance in simplexvirus proteomes was not a consequence of the base composition of their genomes (high G + C content). Conversely, protein function determines the IDR fraction, which is significantly higher in viral proteins that interact with human factors. We also found that the average extent of disorder in herpesvirus proteins tends to parallel that of their human interactors. These data suggest that viruses that interact with fast-evolving, disordered human proteins, in turn, evolve disordered viral interactors poised for innovation. We propose that the high IDR fraction present in simplexvirus proteomes contributes to their wider host range compared with other herpesviruses.